Effect of Lithium Chloride (Licl) Dopant on The Performance of Catalysts for the Oxidative Coupling of Methane - Mamat, M. F.; Mohd Zabidi, N. A.; Bhatia, S.; Megat Ahmad, M. H. A. (IIUM Press, International Islamic University Malaysia, 2000)
The present study reports effects of lithium chloride (LiCl) doping on MgO, La2O3, SnO2, CaO and ZnO catalysts. All the catalysts were prepared by the impregnation method. The catalysts were tested at reaction temperature of 775oC. The feed flow rate of methane, oxygen and nitrogen was carried out in the ratio of 3:1:2 giving a weight hourly space velocity (WHSV) of 0.375 g.s/cm3. La2O3 showed the highest C2+ selectivity among the undoped catalysts. All the catalysts were doped with LiCl to compare their methane conversion, selectivity and product yield. The 2.0 mol% LiCl doped into La2O3 was the best catalyst formulation having achieved 46.7% of C2+ selectivity with CH4 conversion of 29.0% and the increase in selectivity was attributed to the presence of chlorine. Hydrogen production was more pronounced for MgO based catalysts and believed to be generated by surfacecatalyzed reactions.